Analisis Postur Kerja Aktivitas Pengangkatan Karung di PT. Indofood CBP Sukses Makmur Tbk. Cabang Makassar - Arminas Arminas (Jurnal Optimasi Sistem Industri, 2017)
PT. Indofood CBP Sukses Makmur Tbk is a company that works in the field of food processing industry which produces instant noodles, Indomie. At this company, human resource management gives a significant effect on the production sustainability and development. The observation that conducted in PT. Indofood CBP indicates that loading and delivering process are still using the manual procedure which uses human power with loading capacity around 25 kg. The observation focus on two working movement elements used by the screw machine workers consists of bending over when lifting and pouring the wheat flour sack resulted in worker’s frequent complaints related to the waist and backbone problems. The objective of this research is to discover the risk arising from lifting and delivering techniques used by the screw machine workers in PT. Indofood Sukses Makmur Tbk., then analyze the worker’s workload based on the observation result. Rapid Entire Body Assessment (REBA) method was used to analyze the data and it is concluded that lifting and pouring procedures used by the screw machinery workers in PT. Indofood CBP have a high risk of injury since the REBA scores of both activities is 5 or on the third level. This score means that immediate improvement on the working system is needed.